INCLUSION: ILLUSIONS AND REALITY OF THE PROBLEM OF TEACHING SPECIAL CHILDREN IN THE CONDITIONS OF MODERN RUSSIAN SOCIETY - O. Kornilova (Вестник университета)
The arguments confirming the absence of a viable one models of inclusive education at all levels of modern Russian education are presented. The analysis of the current state of education of children with disabilities is made and the factors that prevent the realization and practical realization of inclusive education in Russia are listed. The current problems and tasks facing the education system of modern Russian society in the light of social adaptation and comprehensive support for children with disabilities have been identified.